ANALYSIS OF THE INFLUENCE OF MASS LOSS THROUGH STELLAR WIND, ROTATION, AND OVERSHOOT ON MASSIVE STARS STRUCTURE DURING THEIR EVOLUTIONS, A REVIEW: MAIN SEQUENCE MASSIVE STARS IN SMALL MAGELLANIC CLOUDS - Yoshino, Hiroyuki
Massive stars have a minimum mass of 8 M? and end their lives in a supernova explosion. Scenarios from the birth to death of this star are different for each different mass ranges. In addition to mass variations, it also influenced by the evolutionary parameters such as stellar winds, rotation, and overshoot. These processes have a large effect on the evolution of massive stars and are increasingly influential in stars with higher masses. These parameters have been widely studied, starting from Vink, Meynet and Maeder, Ekstrom et al., Jie Jin, Higgins & Vink. However, these parameters are still not well constrained. Using MESA-Web, star modeling will be carried out with certain star evolution parameters. It aim is to review the effect of each evolutionary parameter and the combined effect of these parameters. Then, these results will be used as a reference in finding the nearest parameter value for the main sequence massive star in the Small Magellanic Cloud. The modeling results show that the effect of each parameter is different in each of the mass under review. The combination effect produces model behavior that is the combined effect of each parameter. From the fitting diagram, the closest parameter values could be obtained for the chosen main sequence massive stars in Small Magellanic Cloud.